Peningkatan Pengetahuan dan Sikap Keluarga Dalam Menurunkan Tingkat Kecemasan Merawat Orang dengan Gangguan Jiwa (ODGJ) - Gusdiansyah, Edo; Syarli, Setiadi; Yuanita Ananda; Deni Maisa Putra (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2025)
People with mental disorders (ODGJ) experience disturbances in cognitive, volitional, affective, and psychomotor aspects that impact their social life, work, and family relationships. The role of the family is very important in the treatment and recovery process of ODGJ patients, but many families experience stress, anxiety, and difficulties in understanding the condition of family members with mental disorders. Lack of knowledge and unsupportive attitudes can hinder the success of care. This community service activity aims to enhance families' knowledge and attitudes in caring for ODGJ to reduce their anxiety levels. The programme was implemented in the Kuranji Health Centre's service area on 8–9 January 2025 through education, training, and support for families of patients using instruments from Notoadmodjo (2013) and the Hamilton Anxiety Rating Scale (HARS). Based on the results of this community service activity, it was found that 80,06% of families experienced mild anxiety, 75,51% had high knowledge, and 50,6% had good family attitudes after receiving health education. It is hoped that through this activity, families can gain a better understanding, adopt a more positive attitude, and be able to provide optimal support in the care process for ODGJ